India then & now - Mukherjee, Rudrangshu; Sanghvi, Vir.; Kapoor, Pramod (New Delhi Roli Books, 2005)
Pictorial representation of India.
India then -- India now.
Texts and photographs of each section in opposite direction and pagination.
Keywords: India -- Pictorial works